A General Equilibrium Model of Insurrections - Grossman, Herschell I. (American Economic Review, 1991)
This paper develops a positive theory of insurrections that treats insurrection and its deterrence or suppression as economic activities that compete with production for scarce resources. The general equilibrium analytical framework reveals how the allocation of labor time among insurrection, soldiering, and production and the probabilistic distribution of income between the peasant families and the ruler's clientele both depend on the technology of insurrection. A central result is that equilibria with more time allocated to insurrection and a higher probability of a successful insurrection have lower production and total income but nevertheless can ha e higher expected income for the peasants.